Android-Based WUZARU Media Boosts Science Learning in Elementary Students: Media WUZARU Berbasis Android Dorong Pembelajaran Sains pada Siswa SD - Vivi Dwi Permatasari; Fitria Nur Hasanah (Academia Open, 2025)
Background: Elementary science education often struggles with abstract topics like "Matter and Its Changes," requiring engaging visual aids. Knowledge Gap: Few effective Android-based tools exist for this purpose. Aim: This study developed and evaluated WUZARU, an Android-based learning media for Grade IV students. Methods: Using the ADDIE model, the media incorporated interactive elements like quizzes and games. Results: Validation by experts rated WUZARU as "very valid," and classroom trials showed significant learning improvements, with average post-test scores reaching 90.36. Novelty: WUZARU bridges theoretical and practical learning through interactive digital media. Implications: The tool demonstrates the potential to enhance science education, fostering critical thinking and independent learning. Highlights: Interactive Learning: WUZARU uses games, quizzes, and multimedia to make abstract science concepts engaging and understandable. Effective Results: Post-test scores improved significantly, demonstrating its impact on learning outcomes. Innovative Approach: Tailored Android-based tools promote critical thinking and independent learning in science education. Keywords: Android-Based Learning, WUZARU, Science Education, Elementary Students, ADDIE Model